2022
DOI: 10.3390/membranes12060591
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low-Pressure Membrane Filtration for Simultaneous Recovery of Detergent and Water from Laundry Wastewater

Abstract: Reusing water and excess detergent from the laundry industry has become an attractive method to combat water shortages. Membrane filtration is considered an advanced technique and highly attractive due to its excellent advantages. However, the conventional membrane filtration method suffers from membrane fouling, which restricts its performance and diminishes its economic viability. This study assesses the preliminary performance of submerged, gravity-driven membrane filtration—under ultra-low trans-membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Indeed, for UE50 and UE10 membranes, the flux decreased from 600 L/m 2 h to 272 L/m 2 h and from 208 L/m 2 h to 165 L/m 2 h, respectively. This finding substantiates previous findings in the literature [ 57 ], wherein it has been shown that detergent solution significantly reduces the flux during the UF process. According to [ 43 ], this observation can be attributed to the adsorption of surfactants on the membrane surface.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Indeed, for UE50 and UE10 membranes, the flux decreased from 600 L/m 2 h to 272 L/m 2 h and from 208 L/m 2 h to 165 L/m 2 h, respectively. This finding substantiates previous findings in the literature [ 57 ], wherein it has been shown that detergent solution significantly reduces the flux during the UF process. According to [ 43 ], this observation can be attributed to the adsorption of surfactants on the membrane surface.…”
Section: Resultssupporting
confidence: 93%
“…It is well known that the UF process is less effective for the retention of low molecular weight substances. With regard to surfactants, the retention degree depends on their type and concentration [ 56 , 57 ]. However, to be complete, it should be noted that after exceeding the critical micelle concentration (CMC), the formed micelles become larger, which facilitates their retention by UF membranes [ 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Where the results of processed wastewater are expected to be reused so that in this way it can minimize the volume of waste produced. Waste treatment can be carried out by applying an ultra-low pressure membrane filtration process with a Gravity Driven Membrane (GDM) system [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…From this illustration, it is expected that when performing membrane filtration, the resulting permeate is water-free from detergents. Previous research conducted by Khery et al [13] for gravity-based polyacrylonitrile ultrafiltration membranes with low pressure explained that filtration in detergent solutions has a deficiency in the membrane's permeability (water flux). This happens because the higher pressure carried out during filtration can result in foulants, so there is a decrease in permeability.…”
Section: Introductionmentioning
confidence: 99%